Coordinating urban and rural development in China learning from Chengdu - Yumin, YE.; LeGates, Richard; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
'The growth of China's cities has astounded the world, but the transformation of its countryside may prove to be even more dramatic. Ye's and LeGates's book provides the first comprehensive case study of how Chinese governance is adapting to changing relations between city and country. Their exposition of urban-rural coordinated development in the municipality of Chengdu, at the forefront of national policy innovation, is a must-read for scholars and practitioners interested in the future of China's vast and populous city-regions.' - Daniel Abramson, University of Washington, US. 'The focus of published narrative on the great Chinese urbanization wave was always going to sharpen - away from the general fascination, assertions, theories and commentaries to specific issues and specific regions. Well here is a first class example of the next generation of urban china books, focusing on topic and city. Chengdu, a city on the foothills of the Himalayas in Western China, has enacted a bold experiment with the institutions and organizations that shape urban-rural interactions. The world, not just China, should be interested in the results as a city-region multi-level government hierarchy grapples with new models for harmonizing property rights between urban and rural areas, allocating government competencies to appropriate levels, constructing strategic infrastructure; and by these and other means, attempts to coordinate growth of urban activities into the countryside while preserving agricultural capacity. Ye and LeGates do a fine job in marshaling data and making sense of it through clear text and compelling arguments. A must read for students and researchers of urban China.' - Chris Webster, University of Hong Kong. 'This extraordinary case study of Chengdu, China breaks new ground in the understanding of 21st century urbanization. Its detailed coverage of critical policy changes and practice illuminates our understanding of the rapid changes and important adaptive responses that China has forged to accommodate massive demographic and economic shifts that this country and many others around the world are experiencing. Its impeccable scholarship and clear explanations make this book the key guide and authoritative reference on this topic.' - Eugenie Birch, University of Pennsylvania, US. 'The new Chinese leadership announced in 2013 that "new approaches of urbanization" should be the future of China. Our experience so far has been limited to the coastal region. The collaboration between Ye Cumin, a scholar based in China with in-depth knowledge, and Richard LeGates, a researcher with extensive western experience, resulted in this fruitful publication, providing insights from Chengdu, about integrated urban-rural development. This is a fascinating story and timely contribution to urban China research.' - Fulong Wu, University College London, UK. 'This book provides a vivid picture of the urban-rural coordinated development of Chengdu, and has important reference value for other developing regions in reducing urban-rural disparity through institutional reform.' - Li Tian, Tongji University. 'Ye and LeGates offer a richly detailed and up-to-date study of Chengdu, China's widely celebrated initiative to integrate urban and rural development. They build upon, but also expand, the pioneering scholarship of Terry McGee on the peri-urban phenomenon. The fate of rural areas surrounding rapidly expanding urban megacities like Chengdu is a global challenge for planners that will benefit from the critical assessment offered in this volume.' - Christopher Silver, University of Florida, US. 'This book presents a promising progress on regional development governance based on ongoing activities in Chengdu. Coordinating urban and rural development is an overwhelming challenge faced by many countries in the world that are urbanizing. The book discusses issues that are uncommon in literature about China, such as reform, public service equity, and grassroots democracy, and is written by a leading scholar on the subject. It will enrich our knowledge about China's development.' - Wilmar Salim, Institut Teknologi Bandung. This detailed study offers a succinct yet comprehensive introduction to China's crucial policy to coordinate urban and rural development. It describes the theoretical, political, and economic reasons why China allowed a large gap between urban and rural incomes, public services, and quality of life to emerge, and the recent national and local government efforts to narrow this inequality. The authors draw primarily on extensive field research and experience in Chengdu, China's leading pilot region for the policy. They describe and explain Chengdu's governmental, administrative, economic, political, and planning system reforms and their accomplishments in clarifying land use rights, rationalizing industrial zones, modernizing agriculture, implementing regional planning, and equalizing infrastructure and services. Coordinating urban and rural development is one of the most pressing problems facing developing countries today. This book places China's experience in context and explains what other cities in China and throughout the developing world can learn from Chengdu as they develop and urbanize. This important book will appeal to academics and policymakers interested in urban planning, economics and development in China, Asia, and elsewhere. It will undoubtedly become an indispensable resource for urbanizing countries throughout the world.
1. Urban-rural development in an urbanizing world -- 2. China's urban-rural relationships and national modernization -- 3. The Chengdu model of coordinated urban-rural development : framework and strategy -- 4. Governance and public administration reform -- 5. Urban and rural planning and development in Chengdu -- 6. Equalizing public services -- 7. Grassroots democracy : the foundation of rural modernization -- 8. Functional zones and economic growth -- 9. Restructuring land, labor, and capital markets -- 10. Chengdu experience's value for China and the challenges for its wider application -- 11. What the world can learn from Chengdu -- 12. Conclusion.
Includes bibliographical references and index.
Keywords: Urbanization -- China -- Chengdu; Community development, Urban -- China -- Chengdu; Rural development -- China -- Chengdu; Electronic books